2019
DOI: 10.1016/j.amj.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital Times Using Helicopters Versus Ground Services for Emergency Patients

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…When distances are short, a rapid response vehicle is used in Finland instead of a helicopter, partly explaining the difference compared to the systems operating only by helicopter to the longer distances. Three of the six bases in Finland are located in mostly urban areas where distances are generally short and the use of helicopter might not result in time saving [31,32]. As shown by our study, the practice of escorting a patient transported in an ambulance is more common in our system compared to other systems [6][7][8].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…When distances are short, a rapid response vehicle is used in Finland instead of a helicopter, partly explaining the difference compared to the systems operating only by helicopter to the longer distances. Three of the six bases in Finland are located in mostly urban areas where distances are generally short and the use of helicopter might not result in time saving [31,32]. As shown by our study, the practice of escorting a patient transported in an ambulance is more common in our system compared to other systems [6][7][8].…”
Section: Discussionmentioning
confidence: 69%
“…As shown by our study, the practice of escorting a patient transported in an ambulance is more common in our system compared to other systems [6][7][8]. However, several studies have demonstrated benefit from timesaving by helicopter transportation in select patient groups [28,29,31]., raising the question whether helicopter transportation should be more frequent.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The greater the distance from the hospital, the more the time that can be saved. As mentioned, only a few studies that compare the slope or curves (between distance and time) of the modalities have been reported, [21,25] and to the best of our knowledge, the current result is the rst curve in Korean HEMS circumstances. Furthermore, the R 2 parameter, which refers to the goodness-of-t of the ideal curve, is higher in HEMS (0.7722 in HEMS vs. 0.6518 in GEMS).…”
Section: Discussionmentioning
confidence: 84%
“…The greater the distance from the hospital, the more the time that can be saved. As mentioned, only a few studies that compare the slope or curves (between distance and time) of the modalities have been reported, [ 22 , 26 ] and to the best of our knowledge, the current result is the first curve in Korean HEMS circumstances. Furthermore, the R 2 parameter, which refers to the goodness-of-fit of the ideal curve, is higher in HEMS (0.7722 in HEMS vs 0.6518 in GEMS).…”
Section: Discussionmentioning
confidence: 94%